Experience in organizing practical work in the Ukrainian language for foreign students (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article summarizes the experience of teaching foreign students the Ukrainian language at Kherson State University. The expediency of four categories of foreign students for distribution in groups during practical work in the class is grounded. This distribution depends on the level of the initial knowledge of both Ukrainian and English or Russian languages, which play the role of linguistic intermediary in the practical work of foreign students in the classroom. The first category includes students with a complete lack of understanding of Ukrainian, Russian or English; The second category includes students with knowledge of English only, without understanding Ukrainian or Russian; the third category includes students with knowledge of the Russian language, but without understanding Ukrainian or English; The fourth category includes students who partially understand the Ukrainian language. The effectiveness of the formation of mixed groups of four categories of foreign students is proved.The methodology of using tutorial help for students who understand Ukrainian, Russian or English is described in the course of practical work in Ukrainian language in mixed groups. The method of organization of practical work in the classroom describes the order of the instructor in the Ukrainian or Russian language of tutor students on the content and methods of performing practical assignments in the classroom. The tutors explain to the compatriots their basic language for doing the practical work and carry out a test task near the board with an oral commentary in two languages – Ukrainian and mother tongue of foreign students. After the tutorial briefing, students begin their independent work on practical assignments in the Ukrainian language. The author of the article describes group forms of organization of practical work of foreign students in classes of Ukrainian language. At the initial stage of studying the Ukrainian language, the mixed group is divided into 2–3 teams of 5–10 people, led by captains-tutors. Captains instruct foreign students about the content and order of the tasks, and also help in the course of the work. Starting from the second year of studying the Ukrainian language, students are united in links of 3–4 people with a link-tutor. This form of organization of work is effective for performing tasks with oral dialogue. Work in pairs is more individual and expedient when performing tasks with scientific texts and preparing scientific reports. One of the students in the pair performs the role of instructor, the second is the executor of practical work.
Keywords: foreign students; practical work in the Ukrainian language; categories of foreign students for distribution in groups; methods of using tutoring for classes; group forms of organization of practical work at class